A comparison of continuous intravenous insulin and subcutaneous insulin among patients with type 2 diabetes and congestive heart failure exacerbation. Issue 1 (January 2015) - Dungan, Kathleen M.; Osei, Kwame; Gaillard, Trudy; Moore, Jared; Binkley, Philip
Abstract Background The study aims to determine whether the route of insulin administration influences glycaemic variability and inflammatory or neurohormonal markers in patients with type 2 diabetes and congestive heart failure (CHF) exacerbation. Methods Patients (n = 65) were randomized to intravenous (IV) insulin (duration 48 h) or subcutaneous (SQ) insulin. Inflammatory cytokines and markers of lipid oxidation, high‐frequency heart rate variability (n = 27) and cardiac impedance (pre‐ejection period, n = 28) were used to estimate parasympathetic and sympathetic tone in patients with valid cardiac data. Glycaemic variability was measured using a continuous glucose monitor. Results Mean glucose was lower (7.7 ± 1.2 vs 9.4 ± 2.7 mmol/L, p = 0.004), coefficient of variation was higher (p = 0.03) and glycaemic lability index was similar on day 1 in the IV group compared with the SQ group, but groups were similar by day 2. The IV group had more confirmed hypoglycaemia (p = 0.005). There were no differences in hospital readmission or hospital length of stay between groups. There were no differences in CHF biomarkers, heart rate variability or pre‐ejection period between groups. Increasing log glycaemic lability index was associated with lower on‐treatment pre‐ejection period (p = 0.03) while increasing coefficient of variation was associated with increasing brain natriuretic peptide (p = 0.004) and paroxonase‐1 (p = 0.02). Other univariable analyses were not significant. Conclusions There were modest, transient differences in glucose control between IV and SQ insulin in hospitalized CHF patients. However, the analyses do not support a link between insulin route and inflammatory markers or autonomic tone. Further study is needed to assess outcomes in hospitalized CHF patients. Copyright © 2014 John Wiley & Sons, Ltd.